2016
DOI: 10.1038/srep36130
|View full text |Cite
|
Sign up to set email alerts
|

Flaw-induced plastic-flow dynamics in bulk metallic glasses under tension

Abstract: Inheriting amorphous atomic structures without crystalline lattices, bulk metallic glasses (BMGs) are known to have superior mechanical properties, such as high strength approaching the ideal value, but are susceptible to catastrophic failures. Understanding the plastic-flow dynamics of BMGs is important for achieving stable plastic flow in order to avoid catastrophic failures, especially under tension, where almost all BMGs demonstrate limited plastic flow with catastrophic failure. Previous findings have sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 60 publications
(99 reference statements)
0
5
0
Order By: Relevance
“…As a new kind of metallic materials, BMGs have unique mechanical and physical properties and a wide range of application prospects [24][25][26]. Although the strength of Zr57 BMG is high, the main cutting force is relatively small, as compared with conventional Zr702.…”
Section: Chip Morphologymentioning
confidence: 99%
“…As a new kind of metallic materials, BMGs have unique mechanical and physical properties and a wide range of application prospects [24][25][26]. Although the strength of Zr57 BMG is high, the main cutting force is relatively small, as compared with conventional Zr702.…”
Section: Chip Morphologymentioning
confidence: 99%
“…By laser surface melting, gradient distribution of both tensile and compressive residual stresses as well as atomic structural changes can also be employed to improve the macroscopic plasticity of BMGs [ 74 , 75 ]. In addition, Wang et al [ 76 ] have obtained an obvious enhancement in the tensile plasticity of BMGs by surface mechanical attrition treatment. Gradient atomic structures were formed during the mechanical attrition process, resulting in a gradient distribution of residual stress with both compressive and tensile stresses.…”
Section: Macroscopic Deformation Behavior Under Gradient Stress DImentioning
confidence: 99%
“…Thereafter, by tailoring single-side notches with varying radii, complex stress fields with varying stress concentration factors have been introduced to some tensile BMG specimens [ 76 ]. Despite different trends in the evolution of amplitudes from compression tests, the flow serrations of the single-side notched BMG specimens also demonstrate power-law criticality within the stable plastic flow stages, similar to the results under compression and nano-indentation tests [ 76 ]. The power-law criticality in BMGs might be a universal rule for all kinds of loading conditions.…”
Section: Tunable Plastic Deformation Behavior Under Tailored Complmentioning
confidence: 99%
See 1 more Smart Citation
“…At room temperature, the plastic deformation of BMGs is highly localized in thin layers of shear bands, demonstrating serrated plastic flows in the stress-strain curves [8,9]. The formation of the serrations is significantly affected by the applied strain rates [10][11][12] and external disturbances, such as the geometric confinement [9,13] and stress gradients [14][15][16]. For example, Schuh et al showed that with increasing loading rates, the plastic deformation in BMGs transits from serrated flows into homogeneous deformation [11].…”
Section: Introductionmentioning
confidence: 99%